DEGREE OF PREPARATION OF SECONDARY SCHOOL STUDENTS IN ADDIS ABEBA FOR THE ETHIOPIAN SCHOOL LEAVING CERTIFICATE EXAMINATION AN EMPERICAL STUDY - Girma, Zewdie (The Ethiopian Journal of Education, 2024)
It h"s been lIIany years since secondary schools .,ith different streaas in their progr"1tIJ48s have been forlll8d. These streallls were established in order to fa cilitate different _anpover needs a t paraprofessional l e vel . In order to seo if the schools have kept these streU2S to a required level, various achieve_nt tests are given . These tests are given as teacher-_ade tests, either as for.ative or su_ative evaluation. This however is not enough to ascertain t he students' colllpletion of the secondary school programes. The Ethiopian School Leaving certificate examination (ESLCE) is therefore given to serve this purpose Tho ESLCE as it has been used for many years is given to determine if the candidates have successfully completed the secondary school programe and to see who thor or not they are able to proceed to a post-secondary one. Although these s trea.s s upposedly prepar e students for various car eers at different levels, they all take ESLCE . But do they al l have opportrmities to prepare themselves adequately for this challenge? This paper , with its 1illlited scope, attempts to investigate just that. To that end s uch variables as tile eighth grade percentile rank of candida tes, period allocations of subjects Commonly offered in secondary schools and qual ifications of teachers of theses Subject s were used. Finally, a ppropriate statistics was employed For analysis .